ScRNA-seq combined with ATAC-seq analysis to explore the metabolic balance mechanism of CCl4-induced liver inflammatory injury - Liu, Hui; Zhang, Yisha; Ning, Shoubin (Frontiers in Immunology, 2025)
BackgroundDrug-induced liver injury (DILI) can provoke inflammation and fibrosis in the liver, potentially leading to severe liver diseases and mortality; however, effective treatments for liver fibrosis remain elusive. The objective of this study was to explore the cellular metabolic mechanism after carbon tetrachloride (CCl4)-induced liver injury.MethodsInitially, we conducted a comprehensive analysis of ATAC-seq, RNA-seq, and scRNA-seq datasets derived from CCl4-induced chronic liver injury in mice. Subsequently, functional enrichment analysis and transcription factor analysis were performed. Finally, the expression changes of key substances and transcription factors were verified by cell and animal experiments.ResultsOur investigation uncovered that hepatocyte histone acetylation intensified with prolonged injury durations. Subsequent functional enrichment analysis identified that fatty acid metabolism as the predominant pathway implicated in hepatocyte damage. The tricarboxylic acid cycle in hepatocytes exhibited partial slowdown and the mitochondrial electron transport chain (ETC) was inhibited in the early stage of CCl4-induced chronic injury. However, in the later stage of injury, there was a gradual restoration of the ETC functionality, coupled with an enhanced capacity for de novo synthesis of fatty acids. This process of metabolic equilibrium restoration may be related to acute lipid accumulation during liver injury repair. Transcription factor analysis found that Zhx2, a crucial suppressor of ETC, experienced sustained increases in chromatin accessibility within injured hepatocytes, but its expression level increased first and then decreased. The key transcriptional repressor Zbtb20 could inhibit the expression of Zhx2, and its expression trend corresponded to that of Zhx2. Cellular experiments demonstrated that CCl4 induced upregulation of acetyl-CoA, Zhx2 and Zbtb20 in a time-dependent manner. The levels of acetyl-CoA and Zbtb20 increased with the duration of injury in animal experiments, but Zhx2 showed a rise in expression only at week 3, while expression returned to normal levels after week 6.ConclusionOur findings contribute to the understanding of the evolution and underlying CCl4-induced inflammatory mechanisms governing hepatocyte inflammatory injury and the subsequent metabolic shift from imbalance toward balance under chronic CCl4 exposure, offering novel perspectives and directions for targeted therapeutic interventions in DILI.